Composition and Manufacturing Effects on Electrical Conductivity of Li/FeS2 Thermal Battery Cathodes. Issue 8 (11th June 2016) - Reinholz, Emilee L.; Roberts, Scott A.; Apblett, Christopher A.; Lechman, Jeremy B.; Schunk, P. Randall
Abstract : Electrical conductivity is key to the performance of thermal battery cathodes. In this work we present the effects of manufacturing and processing conditions on the electrical conductivity of Li/FeS2 thermal battery cathodes. We use finite element simulations to compute the conductivity of three-dimensional microcomputed tomography cathode microstructures and compare results to experimental impedance spectroscopy measurements. A regression analysis reveals a predictive relationship between composition, processing conditions, and electrical conductivity; a trend which is largely erased after thermally-induced deformation. The trend applies to both experimental and simulation results, although is not as apparent in simulations. This research is a step toward a more fundamental understanding of the effects of processing and composition on thermal battery component microstructure, properties, and performance.